Quantitative Analysis of Semicrystalline Blends SAXS Data: Theoretical Modeling versus Linear Correlation Function - Mohamed Fatnassi; Fadhel Ben Cheikh Larbi; Jean Louis Halary (International Journal of Polymer Science)
This paper compares the results yielded by two methods of small-angle X-ray scattering data analysis for semicrystalline polymer blends. The first method is based on the use of a theoretical modeling for isotropic samples and a subsequent curve fitting. The second one is a more familiar method, based on the calculation of the linear one-dimensional correlation function. The experimental material considered for this purpose deals with a series of semi-crystalline blends of poly(vinylidene fluoride) and poly(methyl methacrylate), with a PVDF content covering the range 50 wt%–100 wt%. The results obtained by both calculation methods are systematically confronted to the crystallinity degrees deduced from wide angle X-ray scattering patterns.